UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARANKOOPERATIF TIPE JIGSAW SISWA KELAS VII CMTs DARUL QUR’AN WONOSARI - Nia Galuh Pertiwi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The purposeof this researchwastoimprove the activities andlearning yield in mathematic of student of class VII C MTs Darul Qur’an Wonosari withcooperative learning type Jigsaw. Type Classroom Action Research. The subjects of this research was student of class VII C MTs Darul Qur’an Wonosari totaling 20 student. The objectof this research was activities andmathematics learning yield.Techniques of data collection is usingobservation, tests, and documentation. The results after application of Jigsawmodels,activities andmathematics learning yieldhas increased. This is indicated bythe averagepercentage of observation resultof student learning activities bythe first cycle of 54,29%, and75% in the second cycle.Results ofstudents mathematicslearning yieldtest, the average value ofmathematics learning yieldat 65,5 precycle, the first cycleincreased to68,2 andthe second cycleincreased to 75.